The Satisfaction Level of Employees towards the Prevailing Performance Appraisal System - et. al., Dr. Hemant Bhanawat, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Performance based analysis of an employee and understanding the capabilities of that person, and giving chance to grow is the appropriate technique to enhance employee carrier. Present work deeply concentrated on operative function in the HR sector is evaluated with respect to the Performance Judgement System of the organization. The present study was conducted with the aim to examine the awareness level, satisfaction level, and impact of Performance Appraisal System on employees’ performance. Studies predict that performance-based analysing of employee capabilities gives favourable results and acceptable by employees, and from the results of regression model it is concluded that nearly 91.2 % difference in the dependent variable that is (increase productivity). The study suggested that women’s contribution should be increased in all sectors, which results in the overall empowerment of women. Awareness of employees should be enhanced while assessing the performance appraisal task.